PENDIDIKAN ISLAM MULTIKULTURAL DALAM PERSPEKTIF FILOSOFIS - Ma’mun Mu'min (FENOMENA, 2016)
Since the years 1950 of multicultural education discourse. The reason involves the issue of racism and discrimination against minority groups originating from Africa. 1970s discourse becomes stronger, such as in America, England, Germany, and others. 1980 is seen as the beginning of the emergence of multicultural educational institutions, as initiated by James A Banks et al. The idea of multicultural education is gaining momentum globally as recommended UNISCO in October 1994 in Geneva Switzerland. Among mulikultural educational thinkers of the West, like James A Banks, L. Derman-Sparks, Dawn Gill, Geneva Gay, Christine Sleeter, Peter McLaren, Donna M. Gollnick, Philip Chinn, Will Kymlica, G. Shin and P. Gorski,. Islamic thinkers who carries a lot of Islamic education multicultural issues, such as Fazlur Rahman, "Abdullahi Ahmed An-Na'im, Mohammed Arkoun, Muhammad Shahrour, Humayun Kabir, and 'Ali Shari'ati, and Mamadiou Dia. Of Indonesia, such as Mansour Fakih, H.A.R. Tilaar, Nurcholish Madjid, Azyumardi Azra, and M. Amin Abdullah. Their sincerity in spreading the idea of multicultural education must be bad sometimes, like humuman sentenced to death, was expelled from the country or convicted of apostasy by its opponents. Islamic multicultural education is a response to a variety of global discourse, especially intercultural and multicultural studies that have been developed in the United States and Erofa caused by discriminatory attitudes in the majority to the minority. As in America and Erofa, multicultural Islamic education aims to build a tolerant attitude, pluralistic, humanistic and inclusive towards fellow human beings. But not infrequently Islamic multicultural education has also become a tool for the control authorities, as happened in the world of education in Indonesia in the New Order era. This article is intended to elaborate on Islamic multicultural education in a philosophical perspective.